Wang Yangming on Spontaneous Action, Mind as Mirror, and Personal Depth. Issue 3 (September 2015) - Cocks, Samuel
Abstract: The intention of this paper is to reveal how Wang Yangming's account of spontaneous action includes the development of a sense of personhood and world that both involve historical depth. This will require me to demonstrate how Wang's use of the mirror metaphor does not necessitate a strictly empty account of the human person and their experienced world. I will first elucidate how it is possible to interpret Wang as suggesting that the latter two are poor in depth and identity. Then I will go on to demonstrate that the latter reading does not do justice to Wang's insistence on the rectification and hence stabilization of the person and things across time, past and future.